Multi‐Stakeholder Trade Space Exploration Using Group Decision Making Methodologies. Issue 1 (28th October 2015) - Garber, Melissa; Sarkani, Shahram; Mazzuchi, Thomas A.
Abstract: The focus of this paper is the intersection of Group Decision Making (GDM) methodologies with engineering trade studies, with the goal of improving the efficacy of trade study process models by directly accounting for multiple heterogeneous stakeholders and their preference structures. GDM methodologies are identified and mapped to classes of stakeholders, and to decision making approaches. The discussion includes topics of preference structures, utility theory, ordinality versus cardinality, cooperation, negotiation, and voting procedures. The work will be expanded in the future through development of a framework to standardize both the process of conducting trade studies with multiple stakeholders and the artifacts generated thereby. This will include framework application and validation.